The Development Of Interactive E-book The Diversity of Toga Plants To Train Digital Literacy for 10th High School Student - Masitha, Maurent Maulidiana; Wisanti (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2025)
Digital literacy, from a cognitive perspective, refers to the access, skills, and functional practices necessary to utilize technology effectively for personal, academic, and professional purposes. It plays a vital role for senior high school students by equipping them with the ability to use technology wisely, search for valid information, and develop critical thinking skills that support learning and daily activities. To address this need, this research aimed to develop an interactive e-book on the topic of TOGA (family medicinal plants) diversity to train students' digital literacy skills. The e-book was developed using the 4D model, which includes the Define, Design, Develop, and Disseminate stages. Research parameters included validity, practicality, and effectiveness. Validity was determined through expert judgment, practicality was assessed via readability tests and responses from teachers and students, and effectiveness was measured through concept mastery tests and the implementation of digital literacy indicators. Data were analyze quantitatively using descriptive statistics. The results showed that the e-book achieved a high validity score of 3.8, indicating highly valid in content, presentation, and language. Practicality was demonstrated through a readability score at level 10, with positive responses from teachers (100%) and students (98.5%). Effectiveness was evidenced by a concept mastery score of 88.3% and a digital literacy indicator score of 3.86, both classified as very good. Therefore, the e-book is considered a valid, practical, and effective medium for enhancing student digital literacy.